A hybrid scheme for optimal performance of photovoltaic system converters with multilayer structure. Issue 1 (29th November 2022) - Zand, Mohammad; Nasab, Morteza Azimi; Hanif, Hamid Reza; Ghahri, Muhammad Reza; Padmanaban, Sanjeevikumar; Khan, Baseem
Abstract: The interface of photovoltaic (PV) systems to the grid requires an efficient control strategy to operate, control, and improve power quality. The output voltage of the solar array, which may be accompanied by significant voltage variations, must be controlled and converted to a higher voltage for grid connection applications of photovoltaic system by a DC‐DC converter that commands more attention. Recently, due to the increasing use of renewable sources, multilayer structure with different structures and designs to provide power and stability has been researched because the output voltage of solar arrays is usually low, so it is increasing to DC‐to‐DC converters, needed with optimal interest and efficiency. In this paper, a method to improve the performance of DC–DC converter used in PV system by using a combined design of forward and fly‐back is presented. Due to the fact that isolated converters, flyback, and forward converters have a simple structure and are easy to control, but this converter is affected by high stress voltage. Therefore, this converter cannot be used for high power applications. To solve this problem, it has been improved in the proposed converter with the overlay and triple induction technique, which is a very good improvement on the voltage gain parameters in the short duty cycle. The voltage drop across the semiconductor switch is reduced. The investigations performed that the proposed DC/DC converter in Simulink MATLAB has been simulated. The results show that the suggested converter has an ideal efficiency of roughly 82.86% and provided higher voltage gain, decreased voltage stress, and reduced voltage jumps caused by disconnection. Abstract : In this paper, a method to improve the performance of DC–DC converter used in the PV system by using a combined design of forward and flyback is presented. Due to the fact that isolated converters, flyback, and forward converters have a simple structure and are easy to control, but this converter is affected by high stress voltage.